พฤติกรรมการเคลื่อนตัวของเสาดินซีเมนต์ลึกสำหรับงานโครงสร้างกันดิน - ณัฐกฤต วิสุทธิแพทย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
This research aims to study lateral movement behavior of deep cement mixing column (DCM Column) acting as retaining structures for deep excavation in Bangkok clay. The retaining structures consists of 2 parts as the drainage gates structure and the canal structure. The drainage gate structure is the large reinforced concrete structure having deep excavation of 11.50 m. The temporary retaining structure for deep excavation consists of 9 rows of 0.80 m. deep cement mixing column about 6.34 m. thick depth of DCM column vary from 11.00-18.00 m. The canal structure was designed by using the DCM column wall as the permanent canal wall structure. The DCM Column wall was faced with reinforced concrete sheet 0.30 m. thick and 20 m. long for excavation of 8.00 m. depth. The canal structure consists of 8 rows of 0.8-0 m. DCM column about 5.56 m. thick and 18.00 m. depth. The lateral movements behavior of DCM column for 11.5 m. depth excavation at drainage gate structure was in the cantilever mode for shear strain of DCM wall in the order of 1-2%. When lateral movement of DCM wall was higher with shear strain more than 2%, the DCM wall was failed and each DCM columns was separated. The finite element analysis (FEM) showed that the shear interface between DCM column was in the order of 44- 70% and 20-43% of the undrained shear strength of DCM column for DCM movement with shear strain of 1-2% and more than 2%, respectively. The lateral movement behavior of DCM column for canal structure with depth of excavation only about 4 m. depth shallower than designed depth was in the cantilever mode but without any separating on DCM column. The shear strain of DCM wall was in the order of less than 0.81% and the shear interface between DCM column was closed to the undrained shear strength of ADCM column.